PENGARUH PENGGUNAAN SUMBER ENERGI POWER SUPPLY DAN PWM DC TERHADAP EFISIENSI REAKTOR HIDROGEN - Sulistiawati, Siti; Nasution, Mulkan Iskandar; Ong, Russell (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Hydrogen was chosen as an environmentally friendly alternative energy obtained through the water electrolysis process. In addition to being environmentally friendly, hydrogen also has a high level of electrical energy efficiency. This study aims to determine the effect of the use of electrical energy sources and frequency on the efficiency of a water electrolysis-based hydrogen reactor and to determine the use of energy sources in a hydrogen reactor as an optimal hydrogen producer. The water electrolysis process is influenced by factors such as voltage, current, power, and frequency given to the reactor. Tests were carried out with variations in voltage of 20V, 22V, 24V, 26V, 28V and 30V and frequencies of 23.69kHz, 24.87kHz, 25.64kHz, 26.31kHz, 26.73kHz. The parameters observed include voltage, current, power, H2 gas yield in ppm, temperature, and hydrogen production efficiency in %. The results of the study showed that the effect of using a frequency source was able to achieve a higher efficiency of 41% with an average current of 0.29A, an average power of 7.12 watts, with an average temperature of 30.150C, while the use of a Power Supply Amplifier (PSA) electrical energy source only produced an efficiency of 25%, with an average current of 0.38A, an average power of 9.81 watts, and an average temperature of 28.50C. The optimal value at the highest efficiency was obtained at an optimal frequency of 23.69 kHz with a temperature of 29.00C, a current of 0.20A, a power of 4.8 watts, and an efficiency of 51.57%.Keyword: Electrolysis, Hydrogen, Frequency, Power Supply, EfficiencyAbstrak: Hidrogen dipilih sebagai energi alternatif ramah lingkungan yang diperoleh melalui proses elektrolisis air. Selain ramah lingkungan, hidrogen juga memiliki tingkat efisiensi energi listrik yang tinggi. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan sumber energi listrik dan frekuensi terhadap efisiensi reaktor hidrogen berbasis elektrolisis air dan untuk mengetahui penggunaan sumber energi pada reaktor hidrogen sebagai penghasil hidrogen yang optimal. Proses elektrolisis air dipengaruhi oleh faktor tegangan, arus, daya, serta frekuensi yang diberikan pada reaktor. Pengujian dilakukan dengan variasi tegangan 20V, 22V, 24V, 26V, 28V dan 30 V dan frekuensi pada 23,69kHz, 24,87kHz, 25,64kHz, 26,31kHz, 26,73kHz. Parameter yang diamati meliputi tegangan, arus, daya, hasil gas H2 dalam ppm, suhu, serta efisiensi produksi hidrogen dalam satuan %. Hasil penelitian menunjukkan bahwa pengaruh penggunaan sumber frekuensi mampu mencapai efisiensi lebih tinggi yaitu sebesan 41% dengan arus rata-rata 0,29A, daya rata-rata 7,12watt, dengan suhu rata-rata 30,150C, Sedangkan pada penggunaan sumber energi listrik Power Supply Amplifier (PSA) hanya menghasilkan efisinesi sebesar 25%, dengan arus rata-rata 0,38A, daya rata-rata 9,81 watt, dan suhu rata-rata 28,50C. Nilai optimal pada efisiensi tertinggi diperoleh pada frekuensi optimal 23,69 kHz dengan suhu 29,00C, arus 0,20A, daya 4,8 watt, dan efisiensi 51,57%.Kata kunci: Elektrolisis, Hidrogen, Frekuensi, Power Supply, Efisiensi